Feasibility and challenges in sustaining a community based surveillance system in post-Ebola Sierra Leone - Christina Mergenthaler; Ankie van den Broek; Noor Tromp; Kimberly Nehal; Jip Janssen; Shiyong Wang; T. T. Samba; Mohammed Vandhi; Alpha Augustin Kombo; Osman Sankoh; M. Koblo Kamara; Mirjam I. Bakker (Conflict and Health, 2024)
Abstract Background In outbreak-prone settings, community-based surveillance (CBS) systems can alert health authorities to respond in a timely manner where suspected cases of disease are being reported. After the 2014–2016 Ebola outbreak, the WHO and other stakeholders supported the establishment of CBS in Sierra Leone, for which community health workers (CHW) were trained to collect and report symptoms data of 11 priority health conditions in their communities. Our study objective was to assess feasibility and challenges to sustain CBS in a low resource setting as part of a World Bank evaluation of Sierra Leone’s Ministry of Health and Sanitation’s (MoHS) CBS and electronic Integrated Disease Surveillance & Response (eIDSR) systems. Methods In 2019 we conducted a mixed methods assessment consisting of a household incidence survey, health facility survey, household case verification survey, a costing analysis, and in-depth interviews and focus group discussions with key stakeholders of the CBS system in eight chiefdoms of 4 purposefully selected districts in Sierra Leone. The study period for primary data collection was February through April 2019. We also conducted secondary data analysis of surveillance data in DHIS2 of all 32 chiefdoms. Results In districts where CBS was ‘fully functional’, the number and type of CBS alerts corresponded to the number and type of diseases reported through facility based eIDSR system in the same period. However under-reporting of diarrhea and measles suspects from the community still appeared to occur, and reporting deteriorated when primary health care staff including CHWs reported the stoppage of stipends. The annual budget impact for CBS was estimated at 4.4 million USD in 2018. The majority of costs were made at community level (73%) compared to regional (0.3%), primary health unit (21%), district (4%) and national (2%) level. The most important costs drivers were training of CHWs (59% of total costs) and salaries (including stipends of the CHWs) of human resources (15%). Barriers included sustainable financing of human resources, internet connectivity, as well as limited trainings and supportive supervision, and unsupported transportation costs for CHWs and peer supervisors (PS). CHWs and community members reported that communities are more willing to share information about health issues compared to the pre-CBS implementation period. Conclusions The similarity between CBS and IDSR reports support the possibility that CBS increases the sensitivity of disease surveillance to the level of the community, which would enable local authorities to take early prevention measures when and where impact will be the greatest. Qualitative interviews suggest that CBS has improved the interface between the community and primary level of the health system. However if the barriers to sustainability are left unaddressed, opportunities for CBS to prevent disease outbreaks will go unrealized.